Kuby immunology - Punt, Jenni; Owen, Judith A.; Stranford, Sharon A.; Jones, Patricia P.; Kuby, Janis (New York : W.H. Freeman/Macmillan Learning, 2019)
The 8th edition of 'Kuby Immunology' presents an up-to-date and comprehensive introduction to the principles and findings of immunology. It contains full-colour illustrations, study questions, study aids and much more.
Includes bibliographical references and index.
Keywords: immunity; Immunitet; immune system; Immunsystemet